Treinamento de habilidades sociais e habilidades sociais educativas para mães de crianças com TDAH - Albano, Thayse Loyana Martins (2022)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often have social problems that increase the possibility of social, addictive and attractive changes. Programs teaching social skills and educational social skills to parents of children with ADHD can contribute to changing behavior patterns. The aim of the study was to apply and evaluate an individualized training of social skills and educational social skills for mothers with ADHD in the online modality. Three mothers of children aged between 8 and 10 years old diagnosed with ADHD, but without any other comorbidity, participated in the research. The program months were divided into the following phases: pre-vention, intervention-intervention immediately after the intervention (follow-up). The results were analyzed by the JT method and indicate as main those skills that were the target of the intervention.